Affinity in Adversity: Examining Brand Love and Online Customer Engagement in the Restaurant Industry - José William de Queiroz Barbosa; Maria Carolina Cavalcante Dias; Lissa Valéria Fernandes Ferreira (Tourism & Management Studies)
Previous studies have investigated brand love in restaurants but have not considered the dynamics of online reviews about restaurant brands. To fill this gap, this study aims to understand how consumers with a high level of love towards restaurant brands defend them in the face of negative reviews on social media. This research, carried out in a Brazilian context, adopts a qualitative approach, analysing 3,979 customer reviews sourced from Instagram through sentiment and categorical content analysis. From the dimensions of brand love, the results showed that customers who love restaurant brands react to negative reviews about them on social media, expressing their positive emotional connection with the companies and acting as their defenders. The study shows that for the restaurant segment, it is relevant to have consumers who love the brand once they help mitigate the effects generated by negative comments online. Furthermore, the research highlights how brand love manifests in restaurant brands' digital context.